German radiation oncology’s next generation: a web-based survey of young biologists, medical physicists, and physicians$dfrom problems to solutions - Weissmann, Thomas; Deloch, Lisa; Grohmann, Maximilian; Trommer, Maike; Fabian, Alexander; Ehret, Felix; Stefanowicz, Sarah; Rühle, Alexander; Lettmaier, Sebastian; Putz, Florian; Shariff, Maya; Wegen, Simone; et al. (Strahlentherapie und Onkologie, 2024)
Background Radiation science is of utmost significance not only due to its growing importance for clinical use, but also in everyday life such as in radiation protection questions. The expected increase in cancer incidence due to an aging population combined with technical advancements further implicates this importance and results in a higher need for sufficient highly educated and motivated personnel. Thus, factors preventing young scientists and medical personnel from entering or remaining in the field need to be identified. Methods A web-based questionnaire with one general and three occupation-specific questionnaires for physicians, biologists, and medical physicists working in radiation oncology and research was developed and circulated for 6 weeks. Results While the overall satisfaction of the 218 participants was quite high, there are some points that still need to be addressed in order to ensure a continuing supply of qualified personnel. Among these were economic pressure, work-life balance, work contracts, protected research time, and a demand for an improved curriculum. Conclusion Mentoring programs, improved education, and strengthening the value of societies in radiation sciences as well as translational approaches and more flexible working arrangements might ensure a high-quality workforce and thus patient care in the future.
Online veröffentlicht: 22. Oktober 2024
Gesehen am 24.04.2025